Evaluation of some new hyperbranched polyesters as binding agents for heavy metals. (27th December 2011) - Asaad, J. N.; Ikladious, N. E.; Awad, F.; Müller, T.
Abstract Different generations of hydroxyl and carboxyl terminated hyperbranched polyesters were synthesised and used as heavy metals chelating compounds. The adsorptive capacity of the 3rd generation of the polyesters (G3‐OH, G3‐COOH) as well as that of nanoclay (Nanofil 116) for cadmium removal was determined through adsorption isotherm studies. The highest metal ion removal capacity was observed for G3‐COOH sample. The extent of binding (EOB) values of various generations of hyperbranched polyesters having the same core structure, but different terminal groups, indicated that, irrespective of the type of terminal group, the higher generations are more effective than the lower ones. EOB data can be adequately described by a bidentate coordination model for carboxyl terminated polyesters [each Cd(II) ion coordinates with two carboxyl groups] and tetradentate coordination model for hydroxyl terminated polyesters [1Cd(II)/4OH]. The EOB and selectivity properties of all prepared polyesters towards the heavy metal ions Cd(II), Cu(II), and Pb(II), were investigated under competitive condition. The results showed that the carboxyl terminated polymers exhibit higher binding capacities than those of hydroxyl terminated ones and the selectivity follows the order: Cu(II) > Cd(II) > Pb(II) for all polymer samples, irrespective of the type of terminal group. © 2011 Canadian Society for Chemical Engineering